2019
DOI: 10.1093/advances/nmy069
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene and Metabolic Syndrome: A Systematic Review of the Literature

Abstract: Cardiometabolic risk factors increase the likelihood of cardiovascular disease development by 2-fold. Lycopene, a potent lipophilic antioxidant, may be able to mediate oxidative stress, a mechanism underpinning metabolic syndrome (MetS) and its risk factors. This is, to our knowledge, the first systematic review of the literature with the purpose of investigating the relation between circulating lycopene or dietary intake of lycopene and MetS as well as its risk factors. The review was conducted using PubMed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 48 publications
(78 reference statements)
1
28
0
Order By: Relevance
“…These reported effects are furthermore explained by incorporating details on the molecular mechanism of action of lycopene. The results of the cross-sectional studies are consistent with the findings of previous systematic reviews assessing the relationship between lycopene and vascular risk, metabolic syndrome, prostate, and bladder cancer [ 33 , 34 , 35 , 36 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These reported effects are furthermore explained by incorporating details on the molecular mechanism of action of lycopene. The results of the cross-sectional studies are consistent with the findings of previous systematic reviews assessing the relationship between lycopene and vascular risk, metabolic syndrome, prostate, and bladder cancer [ 33 , 34 , 35 , 36 ].…”
Section: Discussionsupporting
confidence: 88%
“…While in vitro and animal studies show promise for the potential health effects of lycopene, the relationship between lycopene and low-grade chronic inflammation in itself has so far been inconclusive in humans. Various systematic reviews have already been conducted on lycopene and how it affects different diseases and their symptoms, such as prostate and bladder cancer, Cardiovascular risk and metabolic syndrome [ 33 , 34 , 35 , 36 ]. The cross-sectional and intervention studies assessed in these reviews were often inconclusive, and the inconsistency among studies and the type of lycopene tested makes comparison difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the protective role of lycopene in metabolic syndrome has been well-studied. It seems that different metabolic syndrome components can be improved by lycopene supplementation "rather than demonstrating consistent improvement in a single component" [16]. Lycopene can be used in different CVDs, too [17].…”
Section: Introductionmentioning
confidence: 99%
“…Results are supported by previous findings in which a similar dose of lycopene provided by watermelon or tomato juice did not result in improvements in antioxidant capacity or cholesterol levels in middle-aged adults ( 33 ). In contrast, 2 recent systematic reviews reported varying degrees of improvement in lipid profiles after consumption of 100% fruit juice or supplementation with lycopene ( 34 , 35 ). It is plausible that the discrepancy in results may be attributed to differing bioactive compounds as well as the dose and duration of the intervention.…”
Section: Discussionmentioning
confidence: 98%